Charmed mesons with a symmetry-preserving contact interaction - Serna, Fernando E. [UNESP] (2017)
A symmetry-preserving treatment of a vector-vector contact interaction is used to study charmed heavy-light mesons. The contact interaction is a representation of nonperturbative kernels used in Dyson-Schwinger and Bethe-Salpeter equations of QCD. The Dyson-Schwinger equation is solved for the u, d, s and c quark propagators and the bound-state Bethe-Salpeter amplitudes respecting spacetime-translation invariance and the Ward-Green-Takahashi identities associated with global symmetries of QCD are obtained to calculate masses and electroweak decay constants of the pseudoscalar pi, K, D and D-s and vector rho, K*, D*, and D-s* mesons. The predictions of the model are in good agreement with available experimental and lattice QCD data.